Hanan al-cinema : affections for the moving image - Marks, Laura U., 1963- (Leonardo (Series) (Cambridge, Mass.), 2015)
An examination of experimental cinema and media art from the Arabic-speaking world that explores filmmakers' creative and philosophical inventiveness in trying times.